Cross-Cultural Adaptation and Validation of the Polish Version of the Orthognathic Quality of Life Questionnaire (OQLQ) - Małgorzata Gałczyńska-Rusin; Maciej Okła; Martyna Wardak; Małgorzata Pobudek-Radzikowska; Małgorzata Idzior-Haufa; Agata Czajka-Jakubowska (Journal of Clinical Medicine, 2026)
Background/Objectives: Dentofacial deformities may adversely affect facial aesthetics, oral function, psychological well-being, and social functioning. The Orthognathic Quality of Life Questionnaire (OQLQ) is a condition-specific instrument developed to assess these effects, but no validated Polish version has previously been available. This study aimed to translate and culturally adapt the OQLQ into Polish and evaluate its reliability and construct validity, including structural validity. Methods: The OQLQ was translated and culturally adapted in accordance with established guidelines. The study included 161 adults: 49 patients with dentofacial deformities awaiting orthognathic surgery, 55 orthodontic patients without dentofacial deformities, and 57 untreated controls. Internal consistency was assessed using Cronbach’s alpha. Thirty participants completed the questionnaire again after one week to assess test–retest reliability using intraclass correlation coefficients (ICCs) with 95% confidence intervals (CIs). Measurement error was quantified using the standard error of measurement (SEM) and the minimal detectable change at the 95% confidence level (MDC95). Structural validity was examined by confirmatory factor analysis (CFA) of the original four-factor model using diagonally weighted least squares for ordinal items. Known-groups, convergent, and discriminant validity were evaluated using predefined hypotheses. Results: The Polish OQLQ demonstrated excellent internal consistency for the total score (Cronbach’s alpha = 0.957), with domain-level coefficients ranging from 0.879 to 0.948. The total-score ICC was 0.942 (95% CI, 0.88–0.97), and domain ICCs ranged from 0.766 to 0.931. For the total score, the SEM was 3.37 points and the MDC95 was 9.3 points. CFA showed mixed fit (scaled CFI = 0.960, TLI = 0.954, RMSEA = 0.125 [95% CI, 0.115–0.134]; robust SRMR = 0.080), while standardized factor loadings ranged from 0.762 to 0.997. Patients awaiting orthognathic surgery had significantly higher OQLQ scores than both comparison groups (p < 0.001), with large total-score effects versus the non-orthodontic control group (Hedges’ g = 1.55; 95% CI, 1.12–1.99) and the orthodontic group (g = 1.27; 95% CI, 0.85–1.69). Fourteen of the 15 predefined primary construct-validity hypotheses (93.3%) were supported. Conclusions: The Polish OQLQ demonstrated good-to-excellent reliability and satisfactory known-groups, convergent, and discriminant validity. The CFA provided partial rather than unequivocal support for the original four-factor structure. The instrument may be used with appropriate caution to assess condition-specific quality of life in Polish-speaking patients with dentofacial deformities; replication of its structural validity in a larger independent clinical sample and evaluation of responsiveness are warranted.